Geospatial Distribution of Hospital Resources in Regional Trauma Systems (Review of Foreign Literature) - Yu. G. Shapkin; P. A. Seliverstov; N. Y. Stekolnikov (Неотложная медицинская помощь, 2022)
The review presents the results of foreign studies related to geospatial analysis and modeling of the distribution of trauma centers and helicopter emergency medical services in developed regional trauma systems. The optimal number and geographical location of the trauma centers in the region is determined taking into account the timing of the delivery of victims to the trauma centers of a high level, population density, hospitalization of patients with severe trauma, and the frequency of inter-hospital transfers. The distribution of hospital resources of the trauma system should be based on the needs of the population, and vary depending on the geographical and social characteristics of the region.